The long aftermath : cultural legacies of Europe at war, 1936-2016 - Bragança, Manuel, 1973-; Tame, Peter D., 1945- (Studies in contemporary European history., 2016)
"This volume explores the Spanish Civil War and the Second World War in Europe through the cultural artifacts of the times, beginning in 1936. Cultural artifacts include literature, poetry, and cinema"--Provided by publisher